Human Resources Management at Rendani Manokwari Airport - Tamba, Esra; Yertas, Maria (Universitas Negeri Makassar, 2024)
The aim of this studyto investigate the implementation of human resource management (HR) at Rendani Manokwari Airport. The research method used is a qualitative approach with case studies. Data was collected through in-depth interviews with HR managers, employees, and direct observation of HR activities at the airport. Research findings show that Rendani Manokwari Airport has implemented various HR management strategies and practices to support smooth operations and employee satisfaction. These strategies include careful recruitment and selection, employee training and development, fair reward systems, and effective internal communications. However, several challenges such as the need to improve human resource infrastructure and improve technical skills still need to be addressed. This research provides important insights for airport management and related stakeholders to improve the effectiveness and efficiency of HR management at Rendani Manokwari Airport.